Retrospective comparison of the number of screws used for fixation of skeletal anchorage plates in orthodontics, and their failure rates. Issue 10 (December 2018) - Thean, D.; Gebauer, D.; Wan, K.; Vujcich, N.; Goonewardene, M.
Abstract: The aim of this study was to compare the failure rate of fixation of skeletal orthodontic anchorage plates (SAP) with two screws with that of three screws, and to find out if there is a relation between the number of screws used to fix the plates and the failure rate. We reviewed clinical records of 65 patients from five hospitals with 176 SAP, and took into account other factors that may have affected the failure. The overall failure rate was 15/176 (8.5%), and for with two-screw fixation it was 9/86 compared with 6/90 for those with three-screw fixation. Age, sex, and coexisting medical conditions did not affect the failure rate. There was a higher failure rate for those placed in the mandible (11/105) than for those placed in the maxilla (4/71). SAP provide a stable source of skeletal anchorage for orthodontic treatment. Our results show that those fixed with two screws may be marginally more likely to fail than those fixed with three, but further studies are needed to investigate the association between failure and the number of screws used.